The Role of Radiology in Detecting Bone Resorption and Its Impact on Prosthodontic Treatment Success - Dr. Majdi Abu Ramadan; Dr.Mowaffq abdulhamid Shafi; Dr.Afnan Hashem Balkhy; Dr.Bayader baher kurdi; Khulud Kareem Aljadani (International Journal of Medical Toxicology and Legal Medicine, 2024)
The increasing prevalence and complexity of dental conditions necessitate a comprehensive understanding of anatomical and pathological changes in the oral cavity, particularly bone resorption, which significantly impacts prosthodontic treatment success. This review explores the critical role of radiology in detecting bone resorption and elucidates how various imaging modalities, including conventional radiography, computed tomography (CT), and cone-beam computed tomography (CBCT), contribute to enhanced diagnostics and treatment planning in prosthodontics. The limitations of traditional radiographic techniques, such as two-dimensional imaging and potential misinterpretations due to structural superimposition, underline the need for advanced imaging to accurately assess bone architecture. CT and CBCT provide three-dimensional representations, allowing for detailed evaluations of bone quality, quantity, and morphology, which are essential for the selection of appropriate prosthetic interventions. Moreover, the insights gained from radiological assessments inform critical decisions related to implant placement, the necessity for surgical adjuncts like bone grafting, and the ongoing monitoring of post-treatment outcomes. This review highlights that effective integration of radiological evaluations into clinical practice not only optimizes treatment predictability and patient outcomes but also fosters a comprehensive, patient-centered approach in modern prosthodontics. By enhancing the predictability of treatment outcomes, radiology plays an indispensable role in addressing the challenges posed by bone resorption, ultimately contributing to improved patient satisfaction and quality of life in dental rehabilitation.